The knowledge of church leaders in Taung, Mohale’s Hoek about the HIV/AIDS pandemic - Mafisa, Malehana Anna (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.